2017
DOI: 10.1108/he-01-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual physical education course and college freshmen’s health-related fitness

Abstract: Purpose Conceptual physical education (CPE) classes have been widely offered to promote a healthy lifestyle in higher education settings. The purpose of this paper is to examine the effects of a CPE course on health-related fitness (HRF) levels among college freshmen. Design/methodology/approach A pre- and post-test research design was used. In total, 50 freshmen in a US university were enrolled in a 13-week CPE course. Their HRF levels were assessed by the Fitnessgram at the beginning and the end of the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
1
26
2
1
Order By: Relevance
“…The results show that there is a significant improvement in the healthrelated fitness of students who took the PE course. This agrees with studies done on school children [17,[29][30][31][32] and university students [33][34][35][36][37]. Moreover, the current study shows evidence that the benefits of recreational football [38,39] can be obtained to a certain degree in a classroom setting.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results show that there is a significant improvement in the healthrelated fitness of students who took the PE course. This agrees with studies done on school children [17,[29][30][31][32] and university students [33][34][35][36][37]. Moreover, the current study shows evidence that the benefits of recreational football [38,39] can be obtained to a certain degree in a classroom setting.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, there was a difference between this study and the study by Liu et al [33]. They pointed out that flexibility did not significantly improve after their PE program.…”
Section: Discussioncontrasting
confidence: 81%
“…ese joint position data will be used as initial data. After obtaining the preliminary test data and reducing the noise, the data should be processed to filter unnecessary noise and improve the accuracy of data recognition [12]. e common position noise filter passed by the tracking function is based on the time series data and the bone tissue data of 30 data frames between each frame of data collection, with a time interval of 30 mm.…”
Section: Filtering Experiments Of Joint Position Datamentioning
confidence: 99%
“…According to its brochure, the PAW is designed for the children in compliance with the required standards of the Consumer Product Safety Information Acyl/Children’s Product. The PAW is not primarily intended for research purposes; however, the unique ‘group solution’ features that allow end-users to manage and monitor multiple devices at the same time and graphically display the PA data via its companion web and mobile applications have been well adopted by researchers [ 26 , 27 , 28 , 29 , 30 ]. In particular, a recent study that examined the feasibility of PAW for the assessment of PA in children in free-living settings reported that the PAW was better accepted by children compared to other research-grade monitors, owing to its comfortable, waterproof watch-style design and digital display features [ 31 ], which are known to be associated with higher compliance levels in this population group [ 32 ].…”
Section: Introductionmentioning
confidence: 99%